The Continuous Improvement of the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)–CRISPR-Associated Protein System Has Led to Its Highly Efficient Application in Plants - Wanqing Tan; Zhiyuan Wang; Liezhao Liu (Agriculture)
The creation of the CRISPR–Cas system has provided unprecedented opportunities in plant genome research and crop genetic improvement. In recent years, this system has been continuously improved to meet human needs through the expansion and modification of Cas proteins, the diversification of targeting locations, and the optimization of CRISPR vectors. In this review, we systematically describe the Class II Cas proteins that have been used in plants, deactivated Cas9 (dCas9) and its role in transcriptional regulation, precision editing systems, Cas9 protein variants, as well as methods and examples of CRISPR–Cas systems targeting various regions with different breadths. In addition, we outline the optimization plans based on CRISPR constructs that can overcome the pleiotropy of genes or accelerate the generation of transgene-free plants and the applications of CRISPR systems in plant breeding practices. Finally, we discuss the theory and development of “CRISPR plus”, and the integrated application of existing systems in more species.